Creation Of Conditions For Inclusive Tourism In Uzbekistan - Bekzod Saitov (Euro Asian Journal Publishing, 2024)
The article is devoted to the problems and prospects for the development of inclusive tourism in Uzbekistan. The significance of inclusive tourism as a tool for social integration and economic growth is considered. An analysis was conducted of the current state of the country's tourism infrastructure, focusing on the barriers faced by people with disabilities. International experience in creating an accessible environment in the tourism industry, which can be adapted to the conditions of Uzbekistan, has been described. The article proposes measures to modernize the infrastructure, introduce specialized services, increase the awareness of industry workers and use digital technologies. The author concludes that a comprehensive approach and state support are important for creating conditions that correspond to the principles of inclusion, which will allow Uzbekistan to improve the quality of tourism services and enhance its competitiveness on the international stage.
Keywords: inclusive tourism; accessible environment; Uzbekistan